Selectivity in sorption and hydrogenation of methyl oleate and elaidate on MFI zeolites - Philippaerts, An; Paulussen, Sabine; Turner, Stuart; Lebedev, Oleg I.; Van Tendeloo, Gustaaf; Poelman, Hilde; Bulut, Metin; De Clippel, Filip; Smeets, Pieter; Sels, Bert; Jacobs, Pierre (Journal of catalysis, 2010)
Selective catalytic removal of trans-monounsaturated fatty acid methyl esters: nano-sized Pt clusters embedded within Na–ZSM-5 zeolite crystals preferentially catalyze the hydrogenation of methyl elaidate ( trans isomer) from its equimolar mixture with methyl oleate ( cis isomer). [Display omitted] Different zeolites were tested for selective removal of methyl elaidate ( trans isomer) from an equimolar mixture with methyl oleate ( cis isomer). Sorption experiments of the geometric isomers show that only ZSM-5 samples with reduced Al content in the framework are able to discriminate among the bent cis and the linear trans fatty acid methyl esters. Hydrogenation experiments of equimolar methyl oleate and elaidate mixtures at low temperature (65 °C) and high hydrogen pressure (6.0 MPa), using Pt catalysts, confirm this result. Only with a Pt/Na–ZSM-5 catalyst outspoken selectivity for the hydrogenation of the trans isomer is obtained. In order to prepare a selective Pt/ZSM-5 catalyst, the influence of Pt addition (impregnation, ion-exchange and competitive ion-exchange) and Pt activation (different calcination and reduction temperatures) on the Pt-distribution and Pt particle size was investigated using SEM, bright-field and HR TEM, EDX, electron tomography, CO-chemisorption, XPS, XRD, and UV–vis measurements. The best result in terms of hydrogenation activity and selectivity is obtained with a Pt/ZSM-5 catalyst, which is prepared via competitive ion-exchange, followed by slow calcination up to 350 °C under high O 2 flow and a reduction up to 500 °C under H 2. This preparation method leads to a Pt/ZSM-5 catalyst with the best Pt distribution and the smallest Pt clusters occluded in the zeolite structure. Finally, the influence of zeolite crystal size, morphology, and elemental composition of ZSM-5 on hydrogenation activity and selectivity was investigated in detail.